Refinement of the OECD regional typology: Economic Performance of Remote Rural Regions - Vicente Ruiz; Lewis Dijkstra (European Regional Science Association (ERSA), 2010)
To account for differences among rural and urban regions, the OECD has established a regional typology, classifying TL3 regions as predominantly urban (PU), intermediate (IN) or predominantly rural (PR). This typology has proved to be meaningful to better explain regional differences in economic and labour market performance. However, it does not take into account the presence of economic agglomerations if they happen to be in neighbouring regions. Remote rural regions face a different set of problems than rural regions close to a city, where a wider range of services and opportunities can be found. This paper suggests a refinement of the current typology to include a criterion on the accessibility to urban centres. The results show a clear distinction between remote rural regions and rural regions close to a city in terms of declining and ageing population, level of productivity and unemployment. This extended typology, which includes a measure of distance from cities for the population living in a rural area, has been first applied to Europe by the Directorate of Regional Policy of the European Commission and then to North America by the OECD.
Keywords: 330